1989
DOI: 10.1038/ki.1989.155
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis fluid induces change of mononuclear phagocyte proportions

Abstract: Peritoneal macrophages from uninfected continuous ambulatory peritoneal dialysis (CAPD) patients in general show two different, endogenous peroxidase activity (PA) patterns: exudate and negative. This suggests, in accordance with the animal model, that these macrophages are changed proportionately in CAPD patients. This chronic change may be caused by mechanical stimulation alone (massage) or the composition of the dialysis fluid used. Therefore in the rat model both physiological saline and commercial dialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…This pathway could be represented by inflammatory gaps at 37°C, which are not present to the same extent at 19°C [30, 31], causing a markedly increased leakage of LDL and other very large proteins in control animals. Thus, a local sterile inflammatory state seems to be induced by the administration of PD fluids in rats [32]and in patients [33]during a PD dwell. Furthermore, the plasma membranes become ‘stiffer’ at low temperatures, which would decrease the ability of large molecules, like LDL, to pass the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway could be represented by inflammatory gaps at 37°C, which are not present to the same extent at 19°C [30, 31], causing a markedly increased leakage of LDL and other very large proteins in control animals. Thus, a local sterile inflammatory state seems to be induced by the administration of PD fluids in rats [32]and in patients [33]during a PD dwell. Furthermore, the plasma membranes become ‘stiffer’ at low temperatures, which would decrease the ability of large molecules, like LDL, to pass the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Davies et al [4] reported that, when exposed to opsonized zymosan, peritoneal mac rophages from the uninfected CAPD patients show fea tures of maturation and activation, and evidence of the Accepted: July 14.1993 augmented generation of free radicals. Finally, even the intraperitoneal infusion of saline activates peritoneal leu kocytes and this process is more pronounced after exposure of the peritoneum to dialysis fluid [5].…”
Section: Introductionmentioning
confidence: 99%
“…Five days after infection cytospin preparations were made as described (19). The immunoperoxidase staining of acetone-fixed cytospin centrifuge preparations used standard procedures (20) separated by Percoll gradient centrifugation ( Fig. 1).…”
mentioning
confidence: 99%